Unpacking the reasoning task solution approaches of pre-service teachers in the Teacher Education and Development Study in Mathematics. - Alfaro Víquez, Helen (2023)
The knowledge that teachers develop through their academic training greatly influences their performance. It is very difficult for them to promote skills and knowledge in students if they do not have them. Future Costa Rican teachers should be prepared to develop reasoning and argumentation skills in their future students, but there is evidence of low performance in reasoning tasks. In this study, the solutions of 79 Costa Rican future mathematics teachers to two reasoning tasks of the Teacher Education and Development Study in Mathematics (TEDS-M) are analysed in depth using qualitative content analysis. The results showed, among others, that future teachers have deficiencies in retrieving and recognizing key information from statements, and do not monitor whether their justifications are valid. In addition, they evidenced similar reasoning approaches in the solutions.